Boletim Offical do Governo Da Provincia De Macau E Timor (Typografia Mereantil, 1891)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; 2.Damage

Boletim Offical do Governo Da Provincia De Macau E Timor (Typografia Mereantil, 1891)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; 2.Damage

Oeuvres Sacerdotales du Cardinal Pie, Choix de Sermons et D'instructions (Ancienne Librairie Religieuse H. Oudin, 1891)
Keywords: 1.Conservation 保護; 18.Bookworm

INSTITUICOES ELEMENTARES DE RHETORICA PARA USO DAS ESCHOLAS - A. Cardoso Borges de Figueiredo (Livraria Central de J. Diogo Pires, 1891)
Keywords: Condition: Fair; Hard Cover; Teaching

EXPLICACAO LITTERAL E MORAL DAS EPISTOLAS E EVANGELHOS - ANTONIO MOREIRA BELLO (LUGAN AND GENELIOUX, 1891)
Keywords: 18.Bookworm; Condition: Fair; Hard Cover; Religion

EXPLICACAO LITTERAL E MORAL DAS EPISTOLAS E EVANGELHOS - ANTONIO MOREIRA BELLO (LUGAN AND GENELIOUX, 1891)
Keywords: 18.Bookworm; Condition: Fair; Hard Cover; Religion

Les Heros du Christianisme - Beardnard, Marie (Delhomme et Briguet, Editeurs, 1891)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Les Heros du Christianisme - Beardnard, Marie (Delhomme et Briguet, Editeurs, 1891)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Les Heros du Christianisme - Beardnard, Marie (Delhomme et Briguet, Editeurs, 1891)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Les Heros du Christianisme - Beardnard, Marie (Delhomme et Briguet, Editeurs, 1891)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Dictionarium Marianum - Calsanctio, Iosepho (Typis Vaticanis, 1891)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Compendium Introductionis in S. Scripturas, Historicae et Criticae Introductionis - Cornely, Rudolpho (Sumptibus P. Lethielleux, Editoris, 1891)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Historicae et Criticae Intorductionis in U. T. Libros Sacros Compendium - Cornely, Rudolpho (Sumptibus P. Lethielleux, Editoris, 1891)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm

Historicae et Criticae Introductionis in U. T. Libros Sacros Compendium - Cornely, Rudolpho (sumptibus p. lethieleux, editoris, 1891)
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm (Only Cover); 2.Damage

Introductioni In U.T. Libros Sacros Compendium - Cornely, Rudolf S.J. (1891)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Religion

Album-San Ignacio Manresa- 1941- 1891 - Coronas, M. (1891)
Keywords: 1.Conservation 保護; 10.Cover Damage; 14.Missing area; 2.Damage

Bibliotheca, Canonica Iusidica Moralis Theologica - Ferraris, F. Lucii (Ex Typographia Polyglotta, 1891)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Lições práticas da língua portuguêsa: diário de Caturra Junior - Figueiredo, Cândido de (Livraria Ferreira, 1891)
Keywords: Condition: Fair; Hard Cover; Portuguese language Idioms, corrections, errors; languages

Casus Conscientiae in Praecipuas Quaestiones, Theologiae Moralis - Gury, P. Joanne Petro (Apud victor Lecoffre, 1891)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

exposição do dogma catholico - J. M. L. Monsabré (Conférences de Notre-Dame de Paris, 1891)
Keywords: Good

Grammatica Da Lingoa Ingleza - Julio Moreira (Libraria Universal De Magalhaes & Moniz, 1891)
Keywords: 10.Cover Damage; 18.Bookworm (Only Cover); 2.Damage; Condition: Fair; Hard Cover; languages

Commentarius in Dannielem Prophetam, Lamentationes et Baruch - Knabenbauer, Iosepho (Summptibus P. Lethielleux, Editoris, 1891)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

ceuvres oratoires de bossuet - l'abbé J. Lebarq (Desclée de Brouwer, 1891)
Stamp of bibliotheque de nazareth
Keywords: 10.Cover Damage; 18.Bookworm; Poor

Le Symolisme - Landriot (Libraire Victor Lecoffre, 1891)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Oeures Oratoires de Bossuet - Lebarq, L'abbe J. (Desclee, de Brouwer Et Cie, 1891)
Keywords: 1.Conservation 保護; 18.Bookworm (Only Cover); 2.Damage

Considerationes Christianae pro singulis anni diebus - Nepveu, François; Leuckart, Andreas (Typis Societatis Missionum ad Exteros, 1891)
Keywords: 10.Cover Damage; 2.Damage; 22.signature; Condition: Fair; Early works; Meditations; Meditations Early works to 1800; Méditations Ouvrages avant 1800; Religion

Considerationes Christianae pro singulis anni diebus - Nepveu, François; Leuckart, Andreas (Typis Societatis Missionum ad Exteros, 1891)
Keywords: 10.Cover Damage; 2.Damage; 22.signature; Condition: Fair; Early works; Meditations; Meditations Early works to 1800; Méditations Ouvrages avant 1800; Religion

Institutiones Philosophicae Quas Romae In Pontificia Universitate Gregoriana - P. Joanne Josephus Urraburu (Typis Viduæ ac Filiorum a Cuesta, 1891)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Philosophy

La santa Casa de Loyola ... Estudio histórico ilustrado - PEREZ, Rafael (Imprenta del Corazon De Jesus, 1891)
Keywords: 2.Damage; 22.stamp; Condition: Fair; Hard Cover; History; Religion

Anno Christao ou Exercicios devotos para todos os domigos, dias de quaresma e festas Moveis - Petano, D. Justo (Antonio Dourado, Editor, 1891)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Tratado de La Conformidad con la Voluntad de Dios - Rodriguez, Alonso (Libreria Religiosa, Calle de Avino, Num. 20, 1891)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Traite Elemetaire de Chimie - Troost, L. (G. Masson, Editeur, 1891)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Les Auteurs latins expliqués d'après une méthode nouvelle par deux traductions françaises: l une littérale et Juxtalinéaire présentant le mot Francais en regard des mots Latins correspondants l'autre correcte et précédé du texte Latin - Virgil (Librairie Hachette, 1891)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Laudatory poetry, Latin; Poésie élogieuse latine; languages